Penerapan Metode Rapid Application Development (RAD) pada Sistem E-Career Politeknik LP3I Kampus Cirebon Berbasis Aplikasi (Startup) - Aris Riyanto; Ade Johar Maturidi; Khair, Rizaldy (The Indonesian Journal of Computer Science, 2024)
In today's digital era, the Rapid Application Development (RAD) method has shown great potential across various sectors, including education and career development. However, its application in electronic career systems, or E-Careers, remains relatively uncommon. This creates an urgency to conduct research on how the Rapid Application Development (RAD) method can be applied in E-Career systems to enhance efficiency, transparency, and security in the career search process for students. This study aims to apply the Rapid Application Development (RAD) method in the development of a mobile-based E-Career system at Politeknik LP3I Cirebon Campus. One sector that can benefit from the Rapid Application Development (RAD) method is the electronic career system or E-Career. This system aims to facilitate career searches for students in a more efficient and transparent manner. However, a challenge in implementing this system is ensuring that the data shared between different parties is secure and unalterable. The primary goal is to create a system that is not only efficient but also secure and transparent. Thus, students can search for careers more efficiently and transparently, while companies can more easily find the right candidates. Additionally, this research also aims to identify and address challenges in integrating the Rapid Application Development (RAD) method with mobile applications.